2011
DOI: 10.1155/2011/498757
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Elimination of Coproporphyrins Is Dependent onABCC2 Polymorphisms and Represents a Potential Biomarker of MRP2 Activity in Humans

Abstract: MRP2 encoded by ABCC2 gene is involved in the secretion of numerous drugs and endogenous substrates. Patients with Dubin-Johnson syndrome due to mutation in ABCC2 gene have elevated urinary coproporphyrin ratio (UCP I/(I + III)). Here we investigated whether this ratio could serve as a biomarker of MRP2 function. Phenotype-genotype relationships were studied in 74 healthy subjects by measuring individual UCP I/(I + III) ratio obtained on 24-hour urine and by analyzing five common SNPs in ABCC2 gene. The UCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
(41 reference statements)
2
27
1
Order By: Relevance
“…Average percentage of isomer I in our DJS carriers was 43-57%, which is similar to data from literature. 23,24,35 Excretion pattern of coproporphyrin isomers in four patients with dual hereditary jaundice was the same as in other DJS patients with no defect in UGT1A1 (see Table 2). Our findings for coproporphyrin I was 92, 97, 99 and 100% in patients with dual defect compared with 89, 93, 96 and 98% in DJS patients with heterozygous NG_002601.2: g.175492_175493insTA and 89% in DJS patient with the wild-type UGT1A gene.…”
Section: Effect Of a Double Defectsupporting
confidence: 59%
“…Average percentage of isomer I in our DJS carriers was 43-57%, which is similar to data from literature. 23,24,35 Excretion pattern of coproporphyrin isomers in four patients with dual hereditary jaundice was the same as in other DJS patients with no defect in UGT1A1 (see Table 2). Our findings for coproporphyrin I was 92, 97, 99 and 100% in patients with dual defect compared with 89, 93, 96 and 98% in DJS patients with heterozygous NG_002601.2: g.175492_175493insTA and 89% in DJS patient with the wild-type UGT1A gene.…”
Section: Effect Of a Double Defectsupporting
confidence: 59%
“…The results suggested that CPs could be potential endogenous biomarkers of OATP activity in vivo (Benz-de Bretagne et al, 2011;van de Steeg et al, 2012). Indeed, the plasma concentrations of both CP-I and CP-III in cynomolgus monkeys were markedly increased following administration of OATP inhibitors cyclosporine A (100 mg/kg oral) or RIF (15 mg/kg oral) (Shen et al, 2015(Shen et al, , 2016b.…”
Section: Discussionmentioning
confidence: 97%
“…Although CPs have been suggested as putative endogenous markers of OATP1B activity (Benz-de Bretagne et al, 2011;van de Steeg et al, 2012), no studies to date have reported their in vivo disposition, in comparison with known OATP1B probe substrates, after administration of a potent OATP Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary CP isomer ratio has been proposed as a biomarker of MRP2 activity, although there is no in vitro evidence indicating CPs I and III are substrates for MRP2 (Benz-de Bretagne et al, 2011). The proportion of each CP isomer in urine of patients with Dubin-Johnson syndrome Data on plasma concentrations of CPs I and III in healthy subjects are from Kanayama et al (1992).…”
Section: Discussionmentioning
confidence: 99%